2011
DOI: 10.1073/pnas.1105713108
|View full text |Cite|
|
Sign up to set email alerts
|

Expanded methyl-sensitive cut counting reveals hypomethylation as an epigenetic state that highlights functional sequences of the genome

Abstract: Methyl-sensitive cut counting (MSCC) with the HpaII methylation-sensitive restriction enzyme is a cost-effective method to pinpoint unmethylated CpGs at single base-pair resolution. However, it has the drawback of addressing only CpGs in the context of the CCGG site, leaving out the remainder of the possible 16 XCGX tetranucleotides in which CpGs are found. We expanded MSCC to include three additional enzymes to address a total of 5 of the 16 XCGX combinations. This allowed us to survey methylation at about on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 29 publications
1
23
0
Order By: Relevance
“…In order to enrich the CpG-containing regions, the digested fragments are subjected to size selection, followed by sequencing on the next-generation sequencing platform [61]. Methyl-sensitive cut counting (MSCC) with the HpaII methylation-sensitive restriction enzyme is a costeffective method to pinpoint unmethylated CpGs at single-basepair resolution [62].…”
Section: Sequencing Approachesmentioning
confidence: 99%
“…In order to enrich the CpG-containing regions, the digested fragments are subjected to size selection, followed by sequencing on the next-generation sequencing platform [61]. Methyl-sensitive cut counting (MSCC) with the HpaII methylation-sensitive restriction enzyme is a costeffective method to pinpoint unmethylated CpGs at single-basepair resolution [62].…”
Section: Sequencing Approachesmentioning
confidence: 99%
“…Currently, new DNA sequencing technologies are beginning to provide novel insight into genome-wide patterns of DNA methylation (10)(11)(12)(13). Although high-resolution truly genome-wide studies have been limited to a very small sample size, a recent study described the DNA methylation level at 1505 individual sites (loci) in 808 genes in 1628 human genomic DNA samples (14).…”
Section: Introductionmentioning
confidence: 99%
“…Most of the research done to address this problem has focused on the function of promoters and their CpG islands (CGIs), shaping the perception that the CGIs are the hotspots for epigenetic regulation of tissue specific transcriptional activity [9] [10][14]. However, technological advances in methylome analysis have increasingly shown T issue S pecific D ifferentially M ethylated R egions (TS-DMR) as hypo-methylated loci existing outside promoters and CGIs, [15][18]. We recently showed that most of the hypo-methylated loci existing in the liver of an adult mouse are located in introns or intergenic regions and do not meet commonly accepted definitions of CGIs [15].…”
Section: Introductionmentioning
confidence: 99%